Solidarity and particularity: E pluribus unum? A comment on Claus Offe’s Hagar essay, “Political liberalism, group rights, and the politics of fear and trust” - Abraham, David (Hagar: Studies in Society and Culture, 2005)
Even ethnically plural societies require a unum in order to have a state able to keep the peace, allow and protect freedom, encourage participation and belonging, and extract and redistribute resources. That redistribution is needed in order to improve the chances for fairness and justice for individuals. Group rights and federalist devolution are dangerous paths on which to embark as they threaten to preclude toleration, trust and solidarity among compatriots. But no one will embrace a unum from which s/he is excluded. In societies with too much history and too much memory, the creation of a unum may be unsuccessful, leaving separation as the (better) alternative to federalism.